2021
DOI: 10.1108/jfra-04-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and tax avoidance: the case of French companies

Abstract: Purpose The purpose of this paper is to shed light on the effect of tax avoidance on corporate social responsibility performance. It also investigates whether audit quality affects tax avoidance practices by socially responsible performance. Design/methodology/approach Based on a sample of French non-financial companies over the period 2005 to 2016, this paper uses panel data regressions. The authors apply generalized least square panel regression to overcome autocorrelation and heteroscedasticity problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 87 publications
1
10
0
3
Order By: Relevance
“…On the other side, CSR has been shown to affect negatively corporate tax avoidance activities (Davis et al , 2016; Mouakhar et al , 2020; Kovermann and Velte, 2021; Abid and Dammak, 2021). It is considered that more socially responsible firms need to convey transparency, integrity and a good reputation (Lanis and Richardson, 2012; Muller and Kolk, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…On the other side, CSR has been shown to affect negatively corporate tax avoidance activities (Davis et al , 2016; Mouakhar et al , 2020; Kovermann and Velte, 2021; Abid and Dammak, 2021). It is considered that more socially responsible firms need to convey transparency, integrity and a good reputation (Lanis and Richardson, 2012; Muller and Kolk, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…On the other hand, in line with this risk management view of CSR, many studies found that CSR and tax avoidance are positively linked (Abdelfattah and Aboud, 2020;Abid and Dammak, 2022;Alsaadi, 2020;L opez-Gonz alez et al, 2019). Alsaadi (2020) discovered that corporations contribute to CSR to mask their socially irresponsible behaviours of aggressive tax dodging.…”
Section: Corporate Social Responsibility and Tax Avoidancementioning
confidence: 92%
“…Many studies have examined the relationship between CSR and tax avoidance across different countries. While some studies support corporate culture theory (Richardson and Lanis, 2011; Lanis and Richardson, 2012/2015; Hoi et al., 2013; Jones et al., 2017; Karthikeyan and Jain, 2017; Gulzar et al., 2018; Lee, 2020), others support risk management theory (Zeng, 2016; Marsdenia and Martani, 2018; Col and Patel, 2019; Mao, 2019; Abdelfattah and Aboud, 2020; Abid and Dammak, 2021; Jiang et. al., 2022; Khan et.…”
Section: Literature Reviewmentioning
confidence: 99%